2019
DOI: 10.3390/nu11061219
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Considerations for Peripheral Arterial Disease: A Narrative Review

Abstract: Those with peripheral arterial disease (PAD) require important considerations with respect to food and nutrition, owing to advanced age, poor diet behaviours and immobility associated with the disease process and co-morbid state. These considerations, coupled with the economic effectiveness of medical nutrition therapy, mandate that dietetic care plays a vital role in the management of PAD. Despite this, optimising dietetic care in PAD remains poorly understood. This narrative review considers the role of medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 87 publications
(97 reference statements)
2
31
0
1
Order By: Relevance
“…Vegetarian diets are followed by more than 5% of the population and have been recognized as potentially cardio-protective (Delaney et al, 2019). Vegetarian diets emphasize the consumption of fruits, vegetables, nuts and grains with limitation of dairy or meat products (Delaney et al, 2019).…”
Section: Plant Based-vegetarian-vegan Dietsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vegetarian diets are followed by more than 5% of the population and have been recognized as potentially cardio-protective (Delaney et al, 2019). Vegetarian diets emphasize the consumption of fruits, vegetables, nuts and grains with limitation of dairy or meat products (Delaney et al, 2019).…”
Section: Plant Based-vegetarian-vegan Dietsmentioning
confidence: 99%
“…Vegetarian diets are followed by more than 5% of the population and have been recognized as potentially cardio-protective (Delaney et al, 2019). Vegetarian diets emphasize the consumption of fruits, vegetables, nuts and grains with limitation of dairy or meat products (Delaney et al, 2019). Vegeterians are less prone to diabetes mellitus, hypertension, hypercholesterolemia and mortality from ischemic heart disease and stroke (Delaney et al, 2019).…”
Section: Plant Based-vegetarian-vegan Dietsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the mechanism of AAD is still unclear. Previous studies have shown that nutritional status was closely related to peripheral vascular diseases [5,6], such as cervical artery dissection [7]. In addition, in recent years, more and more studies have showed that exposure to famine in early life was signi cantly associated with cardiovascular metabolic diseases, such as diabetes [8], obesity [9], hypertension [10], coronary heart disease [11] and dyslipidemia [12].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the relationship between nutrition and cardiovascular diseases has received more and more attention. It has been shown that nutritional status was closely related to peripheral vascular diseases [10,11], such as cervical artery dissection [12]. In addition, more and more studies have also demonstrated that exposure to famine in early life was signi cantly associated with many cardiovascular metabolic diseases, such as diabetes [13], obesity [14], hypertension [15], coronary heart disease [16] and dyslipidemia [17].…”
Section: Introductionmentioning
confidence: 99%